COMPARISON OF THE OUTCOME OF THE SHORT-AXIS OUT-OF-PLANE ULTRASOUND VERSUS LONG-AXIS IN-PLANE ULTRASOUND GUIDE RADIAL ARTERY CANNULATION AT TERTIARY CARE HOSPITAL, KARACHI - Dr Aftab Ahmed; Dr Rabia Iqtdar; Dr Iftekhar Shah; Dr Kashif Zia; Dr Syed Minhaj Hussain; Muhammad Adeel Khalid (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Radial artery cannulation is essential for hemodynamic monitoring and blood sampling in critical care. Ultrasound guidance improves success rates over palpation, with short-axis out-of-plane (SA-OOP) and long-axis in-plane (LA-IP) as primary techniques. This study compares their outcomes in a tertiary care setting. Objective: To compare the outcomes of SA-OOP versus LA-IP ultrasound-guided radial artery cannulation at a tertiary care hospital in Karachi. Materials and Methods: A randomized controlled trial at the Department of Anesthesia, National Institute of Cardiovascular Diseases, Karachi, from 21st July, 2022 to 22nd January, 2023, enrolled 152 patients (76 per group). Patients aged 18–70 years, ASA II-IV, were included; those with non-consent, negative Modified Allen’s test, or local infection were excluded. Outcomes included first-attempt success, ultrasound location time, and cannulation time, analyzed using SPSS Version 20. Results: SA-OOP showed higher first-attempt success (89.5% vs. 73.7%, p = 0.012), shorter ultrasound location time (6.03 ± 1.81 vs. 15.09 ± 2.45 seconds, p < 0.001), but longer cannulation time (29.47 ± 7.78 vs. 26.29 ± 4.02 seconds, p = 0.002). Conclusion: SA-OOP enhances first-attempt success and localization efficiency, making it preferable for radial artery cannulation.